Participating Locally and Nationally: Explaining the Offline and Online Activism of British Party Members. (August 2019) - Bale, Tim; Webb, Paul; Poletti, Monica
Drawing on survey data on the members of six British parties gathered in the immediate aftermath of the general election of 2015, this article addresses the question of what members do for their parties during campaigns. It identifies a key distinction between traditional forms of activity and more recent forms of online campaign participation. While the well-established general incentives theory of participation continues to offer a useful basis for explaining both types of campaign activism, we find that our understanding is significantly enhanced by considering the impact of national and local political contexts. Whereas the former chiefly adds explanatory value to the model of online participation by party members, the latter considerably improves the model of offline participation.